Cover Image: Nucleation‐controlled semicrystalline morphology of bulk polymers. Issue 4 (24th March 2020) - Schick, Christoph; Androsch, René
Abstract : The crystal nucleation pathway is of huge importance for tailoring the semicrystalline morphology of polymers. For demonstration, the cover images show samples of the biopolymer poly (l ‐lactic acid) crystallized at 130 °C (bottom row) and 140 °C (top row), with the crystallization temperature approached by direct cooling of the melt (right‐column images), or on heating after prior nucleation at 60 °C (left‐column images). In their review article e10036, Christoph Schick and René Androsch present an overview of research activities evaluating the link between the nucleation‐history and semicrystalline morphology, covering numerous polymers and including results obtained using fast scanning chip calorimetry as an extremely useful tool for precisely assuring specific nucleation pathways. As illustrated by the cover images, the combination of chip calorimetry and microscopy conveys quantitative information about the relation between the thermal history and the resulting morphology. (DOI: 10.1002/PCR2.10036 )